Pengaruh Diskon,Kemudahan,Kualitas Informasi Terhadap Keputusan Pembelian Shopee - Laela, Intan Nurjanatul (JEBIM Prima, 2023)
The growth and development of technology in the era of globalization has led to changes in life whereall activities are carried out digitally. One of the conveniences is the ability to shop online like shopee,especially to streamline time in everyday life, so you can shop without coming to the store, makingpayments is also easy to do. Making it easier for consumers to make transactions. The continued growthof e-commerce in Indonesia prompted Shopee to make changes to entice customers to interact morethrough the site. However, apart from convenience, complete product information is also required inorder to avoid product discrepancies in the marketplace that will be sent to consumers. The purpose ofthis study was to describe the effect of discounts, convenience, quality of information on purchasingdecisions of economics and business students at Nahdlatul Ulama Islamic University Jepara. Thisresearch is quantitative by collecting data using a questionnaire. The sampling technique of probabilitysampling with simple random sampling technique is 92 respondents. The results in this study there isno influence between the discount variable on purchasing decisions. While convenience, the quality ofinformation is concluded that there is a significant influence on purchasing decisions.